2020–2021 Vegetable Production Handbook: Chapter 15. Root Crop Production in Florida - Peter J. Dittmar; Eugene J. McAvoy; Richard N. Raid; Hugh A. Smith; Bonnie Wells; Julien Beuzelin; Johan Desaeger; Lincoln Zotarelli; Shouan Zhang; Christian F. Miller; Qingren Wang (EDIS, 2020)
This chapter covers beet, radish, carrot, sweetpotato, cassava, taro, and malanga production.